2012
DOI: 10.4028/www.scientific.net/amm.157-158.476
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adomian Decomposition Method and Differential Transformation Method for Vibration Problems of Euler-Bernoulli Beam

Abstract: In this paper, we compare the Differential transformation method and Adomian decomposition method to solve Euler-Bernoulli Beam vibration problems. The natural frequencies and mode shapes of the clamped-free uniform Euler-Bernoulli equation are calculated using the two methods. The Adomian decomposition method avoids the difficulties and massive computational work inherent in Differential transformation method by determining the very rapidly convergent analytic solutions directly. We found the solution between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Further based upon equations (34) to (36), individual terms given in equation 37are evaluated. The effect of number of terms on accuracy and computational time is analyzed as given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further based upon equations (34) to (36), individual terms given in equation 37are evaluated. The effect of number of terms on accuracy and computational time is analyzed as given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the present work, ADM is used 33 due to its wide application in solving diverse nonlinear problems with very effectual and enhanced accuracy. [34][35][36][37] So far the study of stepped fin is concerned, recently, few studies have been reported using other methods. For example, using linear boundary conditions and by discarding the radiation effect, Arslanturk 38 investigated a stepped fin with variable thermal conductivity using HPM.…”
Section: Introductionmentioning
confidence: 99%